Smartphone application for assessing teacher performance - Marlianawati, Hesty; Suranto, Suranto; Kartowagiran, Badrun (REID (Research and Evaluation in Education), 2023)
This work seeks to design a smartphone application for assessing teacher performance utilizing a 4D development model modified with the Mardapi instrument development model of (1) define (defining); (2) design (deciding instrument requirements, determining application media specifications, creating flowcharts, and creating storyboards); (3) develop (assemble instruments, code, execute tests, evaluate test results, and interpret measurement findings); and (4) disseminate (spread). Proof of the application's viability was established through product testing with 26 principals acting as application users and evaluations by material and media specialists. The content validity of the acquired results was evaluated using the Aiken method, and the construct validity was evaluated using PLS (Partial Least Squares) analysis because the sample size does not have to be large, in accordance with this study where the number of samples is not so large. Using Cronbach's alpha to evaluate the reliability. The results demonstrated that the built application was "possible," as proven by the existing instruments in the valid and trustworthy application. This is proven by the fact that the content validity test utilizing the Aiken method yielded good validity results, with a mean score of 0.80 for material experts and 0.75 for media experts. The construct validity test using PLS (Partial Least Squares) yielded positive results for validity. The estimation of reliability using Cronbach's alpha yields positive findings. Therefore, it can be concluded that the developed application for teacher performance evaluation possesses the features of a valid and trustworthy assessment instrument.